1995
DOI: 10.3109/00365529509089785
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Randomized, Placebo-Controlled Trial of Cisapride in Saudi Arabs with Functional Dyspepsia

Abstract: Cisapride is an effective and well-tolerated treatment for FD in Saudi Arabs. Pharmacogenetic factors are unlikely to play any role in its effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 12 publications
0
21
0
1
Order By: Relevance
“…A dichotomous global dyspepsia outcome was reported in 12 trials (in 11 papers) evaluating 829 patients. 82,[164][165][166][167][168][169][170][171][172][173] The meta-analysis suggested that patients treated with prokinetics were more than twice as likely to have an improvement in dyspepsia symptoms compared with patients receiving placebo (RR reduction 55%; 95% CI, 36 to 78) ( Figure 5). However, there was substantial inconsistency between the trials (test for heterogeneity, Q = 37.7, df = 11, p < 0.0001) and there was evidence of asymmetry in a funnel plot of the trial results ( Figure 6) with larger trials showing smaller treatment benefits.…”
Section: Prokinetic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…A dichotomous global dyspepsia outcome was reported in 12 trials (in 11 papers) evaluating 829 patients. 82,[164][165][166][167][168][169][170][171][172][173] The meta-analysis suggested that patients treated with prokinetics were more than twice as likely to have an improvement in dyspepsia symptoms compared with patients receiving placebo (RR reduction 55%; 95% CI, 36 to 78) ( Figure 5). However, there was substantial inconsistency between the trials (test for heterogeneity, Q = 37.7, df = 11, p < 0.0001) and there was evidence of asymmetry in a funnel plot of the trial results ( Figure 6) with larger trials showing smaller treatment benefits.…”
Section: Prokinetic Therapymentioning
confidence: 99%
“…A total of 17 trials of prokinetic therapy versus placebo were eligible for meta-analysis; 82,164-178 cisapride was investigated in 15 trials; 82,164,165,[167][168][169][170][171][172][174][175][176][177][178] two studies evaluated domperidone, 166,173 and there were no eligible trials that assessed metoclopramide. A dichotomous global dyspepsia outcome was reported in 12 trials (in 11 papers) evaluating 829 patients.…”
Section: Prokinetic Therapymentioning
confidence: 99%
“…Whereas Hiyama et al [54] found significant FD symptom improvement in a meta-analysis comparing pooled prokinetic agents with placebo (N=1,844; PG0.001), numerous placebo-controlled RCTs evaluating individual prokinetic agents demonstrate absent or modest therapeutic significance [55][56][57][58][59].…”
Section: Prokinetic Agentsmentioning
confidence: 99%
“…Five studies of cross-over design which were carried out before 1987 were identi ed (12)(13)(14)(15)(16). Eight studies, all carried out in 1987 or later, used a parallel group design (17)(18)(19)(20)(21)(22)(23)(24). Based on 95% con dence intervals (95% CI) of the differences in treatment success, a signi cant superiority of cisapride over placebo was found in nine studies.…”
Section: Cisapridementioning
confidence: 99%